Daya Terima dan Kadar Asam Thiobarbiturat (TBA) Tempe yang Difortifikasi Zat Besi dan Vitamin A - Rahayu Astuti; Siti Aminah; Agustin Syamsianah (Universitas Muhammadiyah Semarang, 2018)
Tempe is one of Indonesian food which commonly consumed by community and possible as an alternative food that can be fortified with iron and vitamin A. This fortification is an efforts to overcome nutritional anemia. On the other hands, iron addition raises concerns that fortification of iron in fortified tempe can cause oxidative effects. The purpose of this study is to determine the acceptability and levels of thiobarbituric acid (TBA) in iron- fortified tempe and tempe with additional iron+vitamin A. This study use a Completely Randomized Design with 5 experimental groups and 3 replications. The control group was tempe without fortification, while experimental groups 1, 2, 3, 4 were given iron (FeSO) 90 mg, 110 mg, 130 mg and 150 mg/kg of wet soybean. Tempe A is tempe which was given iron fortification, and tempe B was tempe which was given iron+ vitamin A fortification. The results of this study, the acceptability of fortified tempe showed that both tempe A and tempeB, in raw tempe in terms of aroma and color, iron fortified tempe levels of 110 mg and 130 mg were still favored by panelists. Likewise in cooked tempe, the taste, aroma and color that are still preferred are iron levelsof 110 mg and 130 mg. However, tempe with 150 mg of iron is not preferred by panelists. There were no significant differences about levels of thiobarbituric acid (TBA) in tempe without fortification compared to onlyiron-fortified tempe alone and iron+vitamin A-fortified tempe, with more increasing iron levels (90 mg, 110 mg, 130 mg and 150 mg) does not show an increase in TBA levels. The iron (FeSO4) contain with 130 mg/kg of wet soybean is recommended to use in making tempe fortification as an effort to overcome iron-deficiency anemia.